2016
DOI: 10.1177/0143034316649008
|View full text |Cite
|
Sign up to set email alerts
|

Empathy and peer violence among adolescents: Moderation effect of gender

Abstract: The study examined the relationships between empathy and peer violence among adolescents, along with gender as a moderator in these associations. Thereby, multidimensionality of empathy (affective and cognitive empathy) and different forms of violence (physical, verbal, and relational) were considered. The participants were 646 high school students (aged 15-to 19-years-old) from Serbia. The findings revealed that only the cognitive dimension of empathy was related to violence, namely to physical and relational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 77 publications
(131 reference statements)
4
6
0
Order By: Relevance
“…The findings regarding the role of empathy in youth’s engagement in ethnic or non-ethnicity-based victimization show a complex pattern of associations. Supporting previous research (e.g., Dinić et al 2016 ; van Noorden et al 2017 ), the univariate analysis shows that adolescents in any of the non-normative groups (i.e., high ethnic victimization, high non-ethnicity-based victimization, or high on both forms of victimization) have lower empathic concerns and perspective-taking skills than those in the normative group. However, this clear pattern of group differences disappears when the roles of other potential risk factors (i.e., impulsivity, moral disengagement, and attitudes toward immigrants) are taken into account.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The findings regarding the role of empathy in youth’s engagement in ethnic or non-ethnicity-based victimization show a complex pattern of associations. Supporting previous research (e.g., Dinić et al 2016 ; van Noorden et al 2017 ), the univariate analysis shows that adolescents in any of the non-normative groups (i.e., high ethnic victimization, high non-ethnicity-based victimization, or high on both forms of victimization) have lower empathic concerns and perspective-taking skills than those in the normative group. However, this clear pattern of group differences disappears when the roles of other potential risk factors (i.e., impulsivity, moral disengagement, and attitudes toward immigrants) are taken into account.…”
Section: Discussionsupporting
confidence: 85%
“…However, findings on the association between cognitive empathy and antisocial behavior are somewhat inconclusive. Whereas some studies have indicated a negative association between cognitive empathy and aggressive behavior (e.g., Dinić et al 2016 ), others have shown no association (e.g., Jolliffe and Farrington 2011 ; Stavrinides et al 2010 ). Together, the findings suggest that children who victimize their peers are not necessarily incapable of comprehending what their peers feel, but rather that they have an impaired ability to experience what their peers might feel, which indicates that lack of affective empathy may be an important precursor of engagement in peer victimization.…”
Section: Introductionmentioning
confidence: 99%
“…It has been seen that a low affective empathy is a predictor of the involvement as a bully and the other way around (Stavrinides et al, 2010). However, other studies do not show any association between affective empathy and involvement in bullying (Dini et al, 2016).…”
Section: Introductionmentioning
confidence: 85%
“…In some studies, it is said that cognitive empathy is positively associated with a violent behavior in both genders (Caravita et al, 2009; Rieffe and Camodeca, 2016). However, other studies conclude that cognitive empathy is negatively associated with levels of aggression in bullying (Mitsopoulou and Giovazolias, 2015; Dini et al, 2016). One of the few existing longitudinal studies has revealed that cognitive empathy does not predict involvement as a bully or the other way around (Stavrinides et al, 2010).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation